KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA: PENGARUH STRATEGI PEMBELAJARAN ADIS - Galuh Ajeng Dwiastuti; Maifalinda Fatra; Ramdani Miftah (ALGORITMA: Journal of Mathematics Education, 2021)
The critical thinking skill  is part of the 21st century competencies that students need to master. This study aims to analyze the effect of the application of the Argument Driven Inquiry with Scaffolding (ADIS) learning strategy on students' mathematical critical thinking skills. Critical thinking skills measured in this study include the ability of students to formulate problems, provide reasons, make conclusions, and analyze arguments. This study used a quasi-experimental method with a Posttest-Only Control Design. The research was conducted at one of the Bekasi City Junior High Schools in the even semester of the 2019/2020 school year. Sampling using the cluster random sampling technique and data collection techniques using test instruments that have been tested for validity and reliability. The results showed that the mathematical critical thinking skills of students taught with ADIS learning strategies were higher than students taught with conventional learning strategies. Therefore, the ADIS strategy can be used by teachers in learning mathematics at schools/madrasahs in an effort to improve mathematical critical thinking skills.